Assessment of Chickpea (Cicer Arietinum L.) Growth and Yield Component by Application of Local Granular Organic Fertilizer, Peat and Inorganic Fertilizer: Comparative Study - Ali, Shara Salih; Salih Ali, Tara (Kurdistan Journal of Applied Research, 2019)
This study was conducted to increase the productivity of a local variety of chickpea in the Kurdistan region by amending and improving Bakrajo soil with locally made granular organic fertilizer (GOF) and peat and also optimizing the rate of inorganic nitrogen fertilizer (INR). The experimental design used in this study was randomized complete block design with three replications. In this study, Bakrajo soil was treated with two types of organic fertilizer with different rates which were granular organic fertilizer (GOF) and peat. The treatment combinations were soil amendment (SA) with three different rates which were (Soil + 0, 4 and 8 % granular organic fertilizer (GOF)(w/w)) and (Soil + 0, 4 and 8 % peat (w/w)). The inorganic N fertilizer used in this study was applied in three different rates (0, 30 and 60 ppm INR) in form of Urea in water) each rate of INR was measured according to the weight of the soil in the pot. Growth characteristic and yield components were determined in this research. The growth characteristics included the height of plant, number of branches, days to 50% flowering (days), days to physiological maturity (days) and yield components were: pods number /plant, seed number/plant, seeds weight/plant (g), hundred seed weight (g) and grain yield (kg/ha. The result showed that the main effect of SA gave maximum plant height, number of branches, number of pods/plant, number of seeds/plant, weight of seeds/plant, hundred seeds weight and grain yield was observed when the plant is grown under SA of (Soil + 8% GOF) treatment and application of 60 ppm INR also gave highest value of each of growth characteristic and yield components. While the combination of SA (Soil+8% GOF) with 30 ppm INR illustrated maximum value of growth characteristic and yield component. The result of this study illustrates that amending soil with 8% of GOF optimizes the rate of inorganic N fertilizer.